2021
DOI: 10.2967/jnumed.120.243287
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging: PARP-1 and Beyond

Abstract: The genetic code to life is balanced on a string of DNA that is under constant metabolic and physical stress from environmental forces. Nearly all diseases have a genetic component caused by or resulting in DNA damage that alters biology to drive pathogenesis. Recent advancements in DNA repair biology have led to the development of imaging tools that target DNA damage response and repair proteins. PET has been used for early detection of oncogenic processes and monitoring of tumor response to chemotherapeutics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Most radiopharmaceuticals targeting PARP are structurally similar to small molecules olaparib ([ 18 F]-BO, [ 18 F]-PARPi, [ 18 F]-20, [ 123 I/ 131 I]-PARPi, [ 18 F]-PARPi-FL, [ 64 Cu]-PARPi, [ 18 F]-olaparib, [ 18 F]-AZD2461, [ 18 F]-AZD2281, [ 11 C]-PJ34) or rucaparib ([ 18 F]FTT), [ 18 F]-WC-DZ-F, [ 18 F]FE-LS-75, [ 125 I]-KX1, [ 125 I]-KX-02–019, [ 14 C]-rucaparib, [ 211 At]-MM4) [ 40 , 50 , 53 , 56 , 64 , 69 , 78 , 87 , 188 ]. These radiopharmaceuticals were recently reviewed [ 188 , 237 , 238 ]. Three of these PARP radiopharmaceuticals, namely [ 18 F]-PARPi, [ 18 F]FTT, and [ 14 C]-rucaparib have reached the clinical setting ( Table S2 ) [ 61 , 69 , 76 , 85 ].…”
Section: Ddr (Radio)pharmaceuticalsmentioning
confidence: 99%
“…Most radiopharmaceuticals targeting PARP are structurally similar to small molecules olaparib ([ 18 F]-BO, [ 18 F]-PARPi, [ 18 F]-20, [ 123 I/ 131 I]-PARPi, [ 18 F]-PARPi-FL, [ 64 Cu]-PARPi, [ 18 F]-olaparib, [ 18 F]-AZD2461, [ 18 F]-AZD2281, [ 11 C]-PJ34) or rucaparib ([ 18 F]FTT), [ 18 F]-WC-DZ-F, [ 18 F]FE-LS-75, [ 125 I]-KX1, [ 125 I]-KX-02–019, [ 14 C]-rucaparib, [ 211 At]-MM4) [ 40 , 50 , 53 , 56 , 64 , 69 , 78 , 87 , 188 ]. These radiopharmaceuticals were recently reviewed [ 188 , 237 , 238 ]. Three of these PARP radiopharmaceuticals, namely [ 18 F]-PARPi, [ 18 F]FTT, and [ 14 C]-rucaparib have reached the clinical setting ( Table S2 ) [ 61 , 69 , 76 , 85 ].…”
Section: Ddr (Radio)pharmaceuticalsmentioning
confidence: 99%
“…While several comprehensive reviews have previously described preclinical development and translational efforts [ 25 , 27 , 28 , 29 , 30 ], the extensive publication of novel radiolabeled PARPi, as well as clinical study results of the translated PARPi ([ 18 F]FTT and [ 18 F]PARPi), just in the last three years, warrants a systematic overview of the current status in the rapidly expanding field of PARP imaging and therapy. We included all existing probes in this analysis to gain an understanding of the effects of the different structural modifications compared to the parent PARPi on affinity, selectivity, cell permeability, and pharmacokinetic properties.…”
Section: Introduction To Radiolabeled Parp Inhibitorsmentioning
confidence: 99%
“…Several PET radiotracers to image PARP expression have recently been developed [ 13 ]. [ 18 F]FluorThanatrace (FTT), and 18 F-PARPi bind to PARP1, are derived from rucaparib and olaparib, respectively [ 13 ], and are currently being evaluated in breast and ovarian cancers [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several PET radiotracers to image PARP expression have recently been developed [ 13 ]. [ 18 F]FluorThanatrace (FTT), and 18 F-PARPi bind to PARP1, are derived from rucaparib and olaparib, respectively [ 13 ], and are currently being evaluated in breast and ovarian cancers [ 14 , 15 ]. FTT has been developed at our institution, and we have previously reported that FTT has an optimal biodistribution in humans, and the primary route of excretion is through hepatobiliary system [ 16 ].…”
Section: Introductionmentioning
confidence: 99%